Understanding concussion in para athletes with vision impairment - Teodoro, J. J. (University of Waterloo, 2023)
Introduction Sports-related concussions occur in para sport as they do in able-bodied sport. There is evidence to suggest athletes with vision impairment (VI) may be more likely to sustain concussion injuries compared to athletes with other impairment types. However, there is limited understanding of best practices in concussion assessment and management for athletes with VI. Symptoms intrinsic to pre existing conditions in para athletes are also commonly seen in athletes suffering from a concussion, which makes the assessment and management of concussion more challenging in the para athlete population. Perspectives and experiences of VI para sport athletes and coaches with concussion are also poorly understood. The purpose of this project was to understand how concussions are currently assessed and managed in elite para athletes with vision impairment, to move toward establishing clinical practice guidelines and critical research priorities in concussion management for elite athletes with VI. The secondary objective of this thesis was to understand the perspectives, experiences, and knowledge of elite athletes with VI and coaches concerning concussion in VI para sport.